Duration and bandwidth limiting prolate functions, sampling, and applications - Hogan, Jeffrey A. (Applied and Numerical Harmonic Analysis, 2012)
Channel modeling and analysis of multiband signals are becoming increasingly important in the field of communications, and the study of time and band limiting is a crucial component of these processes. This concise but comprehensive monograph is the first to be devoted specifically to this study, providing a thorough investigation of its theory and applications. Via state-of-the-art numerical methods, it develops the tools for applications not only to communications engineering, but also to optical engineering, geosciences, planetary sciences, and biomedicine.  Duration and Bandwidth Limiting begins with a discussion of the Bell Labs theory, both discrete and continuous, and goes on to address various related numerical and analytical techniques. It introduces a number of problems relevant to finite signal processing, and finally builds a theoretical framework for the sampling of time- and band-limited signals. Throughout, the book contains extensive supplemental material, giving greater depth on these subtopics to those who desire it. With an unprecedented breadth of coverage and a careful balance between rigor and readability, Duration and Bandwidth Limiting is a particularly convenient resource both for mathematicians interested in the field and for professional engineers with an interest in theory. While its main target audience is practicing scientists, the book may also serve as useful supplemental reading material for mathematically-based graduate courses in communications and signal processing.